Effects of strontium substitution on structural, electrical and magnetic properties of polycrystalline and nanocrystalline La₀.₆₇(Ca₁₋χSrχ)₀.₃₃MnO₃ - Chang, Sen Choung (2014)
This research is aimed at studying the influences of Sr ions substitution on the structural, electrical and magnetic properties of polycrystalline and nanocrystalline La0.67(Ca1-xSrx)0.33MnO3. The differences between polycrystalline and nanocrystalline samples were discussed. The polycrystalline and the nanocrystalline La0.67(Ca1-xSrx)0.33MnO3 for 0 ≤ x ≤1.0 were synthesized via the solid-state reaction and the sol gel based polymerizable complex method respectively. The X-Ray Diffraction (XRD) measurements were carried out to determine the crystal structure properties. The XRD spectrums revealed that the structural transition from orthorhombic structure to rhombohedra structure took place when the Ca ions were gradually substituted by the Sr ions in both polycrystalline and nanocrystalline samples. The lattice parameters, Mn-O bond length and Mn-O-Mn bond angle were obtained by the Rietveld refinement method. The microstructures for both polycrystalline and nanocrystalline samples were obtained from the Scanning Electron Microscope (SEM). The grain sizes were found in the ranges of 2.83 μm - 8.78 μm and 35.72 nm - 45.38 nm for polycrystalline samples and nanocrystalline samples respectively. The temperature dependences of resistivity and magnetoresistance (MR) were measured by the four point probe method at variable magnetic field range of 0 T - 1 T for both polycrystalline and nanocrystalline samples. The metal-insulator transition temperature (Tp) for polycrystalline samples increased with the substitution of Sr ions. However, the nanocrystalline samples with high surface to volume ratio showed that its Tp varied with the grain size. The intrinsic MR around the Tp and the extrinsic MR at T ≤ Tp were observed in polycrystalline samples. The substitution of Sr ions shifted the intrinsic MR of polycrystalline samples towards higher temperature but lowering its magnitude whereas the intrinsic MR of nanocrystalline samples were suppressed and left behind the extrinsic MR at low temperature. The electrical transport properties for both polycrystalline and nanocrystalline samples were explained by the double exchange interaction within the grain and the spin-polarized tunneling mechanism across the grain boundaries. The highest MR values were found to be -26.79% for polycrystalline x = 0.0 at 244 K and -23.37% for nanocrystalline x = 0.0 at 80 K. At room temperature, the highest MR for polycrystalline samples and nanocrystalline samples were found to be -8.45% at x = 0.4 and -4.19% at x = 1.0 respectively. The field dependences of magnetization for both polycrystalline and nanocrystalline samples were carried out by the Vibrating Sample Magnetometer (VSM). The magnetization increased with the Sr ion substitution for the polycrystalline and nanocrystalline samples due to the increase of the Mn-O-Mn bond angle. The nanocrystalline samples have lower magnetization than that of the polycrystalline samples due to the loss of long-range ferromagnetic ordering in the nanocrystalline samples.